(untitled) (American Journal of Islam and Society, 2017)
In her Feminist Edges of the Qur’an, Aysha Hidayatullah argues that certain Qur’anic verses are incorrigibly male-privileging and are themselves privileged. Hence, egalitarian readings of the Qur’an are unsupported and unsupportable. If, as egalitarians propose, such verses are unjust, then either the Qur’an is not God’s word or God is unjust. By contrast (1) I contend that no evidence suggests any Qur’anic verses are incorrigibly maleprivileging, (2) I provide or indicate egalitarian readings for relevant contenders, (3) I note that no Qur’anic evidence supports the primacy of any such verse. Finally, since controverting egalitarian readings of such verses are available, the logical form of Hidayatullah’s argument merely shows that if they are read to exhibit injustice, those readings cannot be God’s word. Since the Qur’an is God’s word, there is no option but to reread them.